A method for treating and activating the interface of a solid oxide battery and a solid oxide full cell
Patent Information
- Application Number
- CN202611211073.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-11
- Publication Date
- 2026-10-30
AI Technical Summary
本发明提供的HF处理活化固体氧化物电池界面的方法能够解决退火后YSZ和GDC表面与电极之间扩散烧结受限的问题,在不改变各自烧结温度的前提下,能够增强界面与界面间的结合强度
[0016]本发明提供了一种固体氧化物全电池的制备方法,本发明在电解质与燃料电极第一烧结后,在电解质的另一面磁控溅射氧化钆掺杂的氧化铈(GDC)阻挡层并退火。在本发明中,基体YSZ电解质粗糙度的改善能同时提高附着在其表面上的亚微米GDC的粗糙度,即使经过1200℃的退火处理,也能保证界面强度。本发明通过酸处理改善各个界面之间的界面结合,减小界面结合欧姆电阻,从而提升全电池的电化学性能。
Smart Images

Figure CN123018035A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of solid oxide battery technology, specifically to a method for activating the interface of a solid oxide battery using HF treatment and a solid oxide full cell. Background Technology
[0002] Electrolyte-supported solid oxide (SOC) batteries are a mainstream structural design. In this system, the electrolyte layer is the thickest (typically several hundred micrometers), serving as the mechanical support framework for the entire battery. Both the fuel electrode and air electrode are thin films, directly fabricated on either side of the electrolyte. In electrolyte-supported SOC batteries, the fuel electrode and air electrode require diffusion sintering with the high-temperature annealed electrolyte surface. To maintain the porous structure of the electrodes while suppressing grain coarsening, the sintering temperature needs to be controlled between 1000°C (air electrode) and 1300°C (fuel electrode). This temperature limitation can easily lead to high interfacial impedance and low actual contact area, affecting the battery's electrochemical activity.
[0003] For classic yttrium oxide-stabilized zirconia (YSZ) electrolyte systems, a dense gadolinium oxide-doped cerium oxide (GDC) barrier layer is often required between the air electrode (such as strontium lanthanum cobalt oxide (LSC) or strontium lanthanum cobalt ferrite (LSCF)) and the electrolyte to suppress sintering side reactions between the air electrode and YSZ. Magnetron sputtering can produce a thin and dense barrier layer, which requires further annealing. However, after annealing, the GDC surface becomes denser and smoother, weakening the mechanical interlocking between the GDC surface and the air electrode. Furthermore, annealing leads to GDC grain growth, reduced grain boundary area, and decreased interfacial activity, which is detrimental to forming a good bond with the electrode particles. Summary of the Invention
[0004] In view of this, the purpose of this invention is to provide a method for activating solid oxide battery interfaces using HF treatment and a solid oxide full cell. The method for activating solid oxide battery interfaces using HF treatment provided by this invention can solve the problem of limited diffusion sintering between the YSZ and GDC surfaces and the electrodes after annealing, and can enhance the bonding strength between interfaces without changing their respective sintering temperatures.
[0005] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a method for activating the interface of a solid oxide battery using HF treatment, comprising the following steps: Yttrium-stabilized zirconium oxide was immersed in HF solution and acid-etched, followed by water washing and sonication to obtain activated yttrium-stabilized zirconium oxide.
[0006] Preferably, the yttrium-stabilized zirconium oxide is annealed yttrium-stabilized zirconium oxide; In the yttrium-stabilized zirconium oxide, the doping amount of yttrium oxide is 3~8 mol.
[0007] Preferably, the mass concentration of the HF solution is 24.4% to 24.6%. The acid etching treatment is performed at a temperature of 20-25°C for a time of 1-120 minutes.
[0008] Preferably, the power of the ultrasound is 100~180W and the duration is 10~30min.
[0009] This invention provides a method for preparing a solid oxide full cell, comprising the following steps: Following the above method, yttrium oxide-stabilized zirconium oxide electrolyte with activation treatment was obtained; A fuel electrode is printed on one side of the activated yttrium oxide-stabilized zirconium oxide electrolyte, and a first sintering is performed. After the first sintering, a gadolinium oxide-doped cerium oxide barrier layer is magnetron sputtered on the other side, followed by annealing; After annealing, an air electrode is printed on the surface of the gadolinium oxide-doped cerium oxide barrier layer, followed by a second sintering to obtain a solid oxide full cell.
[0010] Preferably, the thickness of the activated yttrium oxide-stabilized zirconium oxide electrolyte is 80~95μm.
[0011] Preferably, the fuel electrode comprises a NiO-YSZ fuel electrode, wherein the mass content of NiO in the NiO-YSZ is 50-60%; The thickness of the fuel electrode is 14~16μm; The first sintering atmosphere is air atmosphere, the first sintering temperature is 1200~1400℃, and the holding time is 1~3h.
[0012] Preferably, in the gadolinium-doped cerium oxide, the gadolinium doping amount is 10~20 mol%; The thickness of the gadolinium oxide-doped cerium oxide barrier layer is 400~600 nm; The annealing atmosphere is air, the annealing temperature is 1000~1300℃, and the holding time is 1~3h.
[0013] Preferably, the air electrode comprises a strontium lanthanum cobalt oxide air electrode with a thickness of 15~20 μm; The atmosphere for the second sintering is air, the temperature for the second sintering is 900~1000℃, and the holding time is 1~3h.
[0014] This invention provides a solid oxide full cell prepared by the above-described preparation method.
[0015] This invention provides a method for activating the interface of a solid oxide battery using HF treatment, comprising the following steps: immersing yttrium-stabilized zirconium oxide (YSZ) in an HF solution for acid etching, followed by water washing and ultrasonication, to obtain activated yttrium-stabilized zirconium oxide. In this invention, HF treatment increases the surface roughness of annealed YSZ and gadolinium-doped cerium oxide (GDC), thereby increasing the contact area between interfaces, enhancing interfacial bonding strength, reducing interfacial bonding ohmic resistance, and thus improving the electrochemical performance of the full cell. Specifically, acid etching occurs simultaneously at the grain boundaries and within the grains of YSZ, with faster etching at the grain boundaries. As the etching time increases, the average grain size gradually decreases. This invention, through ultrasonic treatment, effectively removes elemental segregation and residual fluorine (F) from the YSZ surface.
[0016] This invention provides a method for preparing a solid oxide full cell. After the electrolyte and fuel electrode are first sintered, a gadolinium oxide-doped cerium oxide (GDC) barrier layer is magnetron sputtered onto the other side of the electrolyte and then annealed. In this invention, the improved roughness of the YSZ electrolyte substrate simultaneously increases the roughness of the submicron GDC adhering to its surface, ensuring interfacial strength even after annealing at 1200°C. This invention improves interfacial bonding between interfaces through acid treatment, reducing interfacial bonding ohmic resistance and thus enhancing the electrochemical performance of the full cell. Attached Figure Description
[0017] Figure 1 The microstructure and elemental distribution of YSZ surface after HF pickling; Figure 2 A comparison of the surface roughness of YSZ at different pickling times; Figure 3 These are morphological images of the barrier layer before and after annealing; Figure 4 The graph shows the surface roughness changes of YSZ surface after pickling for different times and GDC surface after annealing. Figure 5 The results show the performance of the full cell under different acid treatment times. Detailed Implementation
[0018] This invention provides a method for activating the interface of a solid oxide battery using HF treatment, comprising the following steps: Yttrium-stabilized zirconium oxide (YSZ) was immersed in HF solution and acid-etched, followed by water washing and sonication to obtain activated yttrium-stabilized zirconium oxide.
[0019] In this invention, the yttrium-stabilized zirconium oxide is preferably annealed yttrium-stabilized zirconium oxide. In this invention, the yttrium doping content in the yttrium-stabilized zirconium oxide is preferably 3-8 mol%, more preferably 4-6 mol%, and even more preferably 5 mol%. In this invention, the surface roughness Ra of the yttrium-stabilized zirconium oxide is preferably 14-18 nm, more preferably 16-17 nm.
[0020] In this invention, the mass concentration of the HF solution is preferably 24.4-24.6%, more preferably 24.5%. In this invention, the preparation method of the HF solution preferably includes the following steps: mixing 48.8-49.2% HF and deionized water at a volume ratio of 1:1.
[0021] In this invention, the acid etching treatment is preferably performed at a temperature of 20-25°C and for a time of 1-120 min, more preferably 5-90 min, further preferably 10-60 min, and even more preferably 20-40 min. In this invention, the washing is preferably performed by immersion in deionized water.
[0022] In this invention, the ultrasonic power is preferably 100-180W, more preferably 120-150W; the time is preferably 10-30min, more preferably 20min. The ultrasonic treatment in this invention removes the insoluble YF3 octahedrons generated by the reaction of HF and YSZ, and further eliminates residual F elements on the surface.
[0023] In this invention, the surface roughness Ra of the yttrium oxide-stabilized zirconium oxide after activation treatment is preferably 19~60 nm, more preferably 20~40 nm.
[0024] This invention provides a method for preparing a solid oxide full cell, comprising the following steps: Following the above method, yttrium oxide-stabilized zirconium oxide electrolyte with activation treatment was obtained; A fuel electrode is printed on one side of the activated yttrium oxide-stabilized zirconium oxide electrolyte, and a first sintering is performed. After the first sintering, a gadolinium oxide-doped cerium oxide barrier layer is magnetron sputtered on the other side, followed by annealing; After annealing, an air electrode is printed on the surface of the gadolinium oxide-doped cerium oxide barrier layer, followed by a second sintering to obtain a solid oxide full cell.
[0025] In this invention, a fuel electrode is printed on one side of the activated yttrium oxide-stabilized zirconia electrolyte, followed by a first sintering. In this invention, the thickness of the activated yttrium oxide-stabilized zirconia electrolyte is preferably 80-95 μm, more preferably 85-90 μm. In this invention, the fuel electrode preferably comprises a NiO-YSZ fuel electrode, wherein the mass content of NiO in the NiO-YSZ is preferably 50-60%, more preferably 55%. In this invention, the thickness of the fuel electrode is preferably 14-16 μm, more preferably 15 μm.
[0026] In this invention, the printing is preferably screen printing, and the number of screen printing layers is preferably 5. After each layer is printed, it is dried at 140°C before printing the next layer. In this invention, the first sintering is preferably diffusion sintering, and the first sintering is preferably carried out under air conditions. The temperature of the first sintering is preferably 1200~1400°C, more preferably 1300°C, and the time is preferably 1~3 hours, more preferably 2 hours. In this invention, the heating rate to the first sintering temperature is preferably 3°C / min. The purpose of the first sintering in this invention is to promote the formation of a stable and continuous interfacial bond between the fuel electrode and the electrolyte.
[0027] In this invention, after the first sintering, a gadolinium oxide-doped cerium oxide barrier layer is magnetron sputtered onto the other side of the yttrium oxide-stabilized zirconium oxide electrolyte, followed by annealing. In this invention, the gadolinium doping amount in the gadolinium-doped cerium oxide is preferably 10-20 mol%, more preferably 15 mol%. In this invention, the thickness of the gadolinium oxide-doped cerium oxide barrier layer is preferably 400-600 nm, more preferably 500 nm. In this invention, the annealing atmosphere is preferably air, the annealing temperature is preferably 1000-1300℃, more preferably 1100-1200℃, the holding time is preferably 1-3 h, more preferably 2 h, and the heating rate to the annealing temperature is preferably 2.5℃ / min. The purpose of this annealing in this invention is to improve the crystallinity and density of the GDC barrier layer.
[0028] In this invention, after annealing, an air electrode is printed on the surface of the gadolinium oxide-doped cerium oxide barrier layer, followed by a second sintering to obtain a solid oxide full cell. In this invention, the air electrode preferably comprises a strontium lanthanum cobalt oxide air electrode, with a thickness preferably 15-20 μm, more preferably 16-18 μm. In this invention, the printing is preferably screen printing, with a preferred number of screen printing layers of 5. After each layer is printed, it is dried at 140°C before printing the next layer. In this invention, the second sintering is preferably diffusion sintering, the atmosphere for the second sintering is preferably air, the temperature for the second sintering is preferably 900-1000°C, more preferably 950°C, and the holding time is preferably 1-3 hours, more preferably 2 hours. The purpose of the second sintering in this invention is to achieve a strong interfacial bond between the air electrode and the GDC barrier layer.
[0029] This invention provides a solid oxide full cell prepared by the above-described method. In this invention, the solid oxide full cell includes a solid oxide electrolyte, a fuel electrode located on one side of the solid oxide electrolyte, a barrier layer located on the other side of the solid oxide electrolyte, and an air electrode. The solid oxide electrolyte is a yttrium oxide-stabilized zirconium oxide electrolyte after HF activation treatment, with a thickness of 80-95 μm, more preferably 85-90 μm. The fuel electrode is preferably a NiO-YSZ fuel electrode, with a thickness of 14-16 μm, more preferably 15 μm. The barrier layer is preferably a gadolinium oxide-doped cerium oxide barrier layer, with a thickness of 400-600 nm, more preferably 500 nm. The air electrode is preferably a strontium lanthanum cobalt oxide air electrode, with a thickness of 15-20 μm, more preferably 16-18 μm.
[0030] The following detailed description, in conjunction with embodiments, illustrates the method for activating the interface of a solid oxide battery using HF treatment and the solid oxide full cell provided by the present invention. However, these descriptions should not be construed as limiting the scope of protection of the present invention.
[0031] Example 1 A method for activating the interface of a solid oxide battery using HF treatment comprises the following steps: 49% HF and deionized water were mixed at a volume ratio of 1:1. YSZ electrolyte (doped with 3 mol% yttrium oxide Y2O3) was immersed in the diluted HF solution for 0 (untreated), 15, 30, 60, and 120 minutes. The residual HF was washed away by soaking in deionized water. Then, YSZ was immersed in deionized water and ultrasonically cleaned at 150W for 20 minutes to remove the insoluble acid pickling product YF3 from the surface.
[0032] The microstructure and elemental distribution of the YSZ surface after HF pickling are as follows: Figure 1 As shown, Figure 1In the figure, (a) shows the surface morphology of YSZ after pickling for different times; (b) shows the elemental distribution of YSZ surface after pickling for 120 minutes.
[0033] The surface energy spectrum mapping results of YSZ with different pickling times are shown in Table 1: Table 1. Energy spectral mapping results of YSZ surface at different pickling times.
[0034] Depend on Figure 1 As can be seen in (a), acid etching occurs simultaneously at the YSZ grain boundaries and within the grains, with the grain boundaries being etched at a faster rate. As the etching time increases, the average grain size gradually decreases. Figure 1 As shown in (b) and Table 1, the semi-quantitative energy dispersive spectroscopy analysis results indicate that the YSZ surface treated with acid for 120 minutes after ultrasonic cleaning did not show obvious elemental segregation or F element residue, demonstrating the effectiveness of ultrasonic cleaning and that HF acid etching does not change the intrinsic chemical composition of the YSZ surface.
[0035] The surface roughness comparison of YSZ after pickling for different times is shown in the figure below. Figure 2 As shown, Figure 2 In the image, (a) shows the 3D roughness morphology obtained from atomic force microscopy (AFM); (b) shows the 2D roughness distribution. Figure 2 According to the atomic force microscopy results, as the acid etching time increases, the surface roughness of YSZ first increases exponentially, and then begins to decrease, reaching the maximum roughness level at 60 minutes of acid treatment.
[0036] Example 2 A method for preparing a solid oxide full cell, comprising the following steps: After acid washing, a NiO-YSZ (55wt% NiO + 45wt% YSZ) electrode (14μm thick) was screen-printed on one side of the YSZ electrolyte (85μm thick) as a fuel electrode. After drying, the electrode was sintered in a muffle furnace at 1300℃ for 2 hours. Then, a 500nm thick GDC barrier layer (20mol% gadolinium doping) was magnetron sputtered on the other side, and annealed at 1200℃ for 2 hours. Following annealing, an LSC air electrode (18μm thick) was screen-printed on the GDC surface and diffusion sintered at 1000℃ for 2 hours.
[0037] To prevent the formation of an insulating strontium zirconate phase through the reaction between the Sr-containing air electrode and the YSZ electrolyte, after diffusion sintering of the electrolyte and fuel electrode at 1300℃, a 500nm thick GDC barrier layer was magnetron sputtered onto the other side of the electrolyte and annealed at 1200℃. The morphology of the barrier layer before and after annealing is as follows: Figure 3 As shown. Figure 3In the figure, (a) shows the surface morphology before annealing; (b) shows the surface morphology after annealing at 1200℃; and (c) shows the 3D roughness morphology after annealing at 1200℃. The surface roughness variations of YSZ surfaces after pickling for different times and GDC surfaces after annealing are shown in the figure. Figure 4 As shown, Figure 4 (a) shows the surface roughness change of YSZ at different acid treatment times, and (b) shows the surface roughness change of GDC after annealing at 1200℃ with acid etching time. It can be seen that improving the roughness of the YSZ substrate electrolyte can simultaneously improve the roughness of the submicron GDC attached to its surface, even after annealing at 1200℃. With increasing acid etching time of the substrate electrolyte, the surface roughness of the annealed GDC remains largely unchanged before 15 minutes of acid treatment, and then gradually increases logarithmically. The increased surface roughness of well-annealed YSZ and GDC helps to increase the contact area between interfaces and enhance interfacial bonding strength.
[0038] Performance test results of the full cell under different acid treatment times are as follows: Figure 5 As shown, Figure 5 The test conditions were: 850℃, 50mL of pure hydrogen gas was introduced into the fuel electrode side, and 200mL of air was introduced into the air electrode side. Figure 5 In the figures, (a) is the linear sweep voltammetry curve and (b) is the electro-impedance spectroscopy (EIS) plot. The results show that all experimental groups treated with surface acid outperformed the untreated full cells. With increasing electrolyte etching time, the full cell performance first increased and then decreased. The full cell treated with acid for 15 minutes exhibited the best performance, with a maximum power density of 493 mW / cm³ under test conditions at 850℃. 2 The untreated battery only has 450mW / cm². 2 Analysis of the impedance spectroscopy (EIS) results shows that this performance improvement mainly comes from the acid treatment improving the interfacial bonding between various interfaces, thereby reducing the ohmic resistance of the full cell.
[0039] In summary, this invention increases the bonding strength between interfaces of a solid oxide battery by etching the electrolyte surface with HF for a short time. This can activate the sintering activity of well-annealed YSZ and GDC surfaces, improve surface roughness, reduce interfacial bonding ohmic resistance, and thus enhance the electrochemical performance of the full cell.
[0040] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for activating the interface of a solid oxide battery using HF treatment, characterized in that, Includes the following steps: Yttrium-stabilized zirconium oxide was immersed in HF solution and acid-etched, followed by water washing and sonication to obtain activated yttrium-stabilized zirconium oxide.
2. The method according to claim 1, characterized in that, The yttrium-stabilized zirconium oxide is annealed yttrium-stabilized zirconium oxide; In the yttrium-stabilized zirconium oxide, the doping amount of yttrium oxide is 3~8 mol.
3. The method according to claim 1, characterized in that, The HF solution has a mass concentration of 24.4% to 24.6%. The acid etching treatment is performed at a temperature of 20-25°C for a time of 1-120 minutes.
4. The method according to claim 1, characterized in that, The ultrasound power is 100~180W, and the duration is 10~30min.
5. A method for preparing a solid oxide full cell, characterized in that, Includes the following steps: According to the method described in any one of claims 1 to 4, an activated yttrium oxide-stabilized zirconium oxide electrolyte is obtained; A fuel electrode is printed on one side of the activated yttrium oxide-stabilized zirconium oxide electrolyte, and a first sintering is performed. After the first sintering, a gadolinium oxide-doped cerium oxide barrier layer is magnetron sputtered on the other side, followed by annealing; After annealing, an air electrode is printed on the surface of the gadolinium oxide-doped cerium oxide barrier layer, followed by a second sintering to obtain a solid oxide full cell.
6. The preparation method according to claim 5, characterized in that, The thickness of the activated yttrium oxide-stabilized zirconium oxide electrolyte is 80~95μm.
7. The preparation method according to claim 5, characterized in that, The fuel electrode includes a NiO-YSZ fuel electrode, wherein the mass content of NiO in the NiO-YSZ is 50-60%; The thickness of the fuel electrode is 14~16μm; The first sintering atmosphere is air atmosphere, the first sintering temperature is 1200~1400℃, and the holding time is 1~3h.
8. The preparation method according to claim 5, characterized in that, In the gadolinium-doped cerium oxide, the gadolinium doping amount is 10~20 mol%; The thickness of the gadolinium oxide-doped cerium oxide barrier layer is 400~600 nm; The annealing atmosphere is air, the annealing temperature is 1000~1300℃, and the holding time is 1~3h.
9. The preparation method according to claim 5, characterized in that, The air electrode includes a strontium lanthanum cobalt oxide air electrode with a thickness of 15~20μm; The atmosphere for the second sintering is air, the temperature for the second sintering is 900~1000℃, and the holding time is 1~3h.
10. A solid oxide full cell prepared by the preparation method according to any one of claims 5 to 9.